A Matter of Intercultural Communication: Perspectives of International Students at a University in South Africa - Rawjee, V.P.; ., M. Maharaj (Journal of Economics and Behavioral Studies, 2013)
The end of apartheid in South Africa in 1994 saw many higher education institutions identifying opportunities to increase their intake of international students by introducing student exchange programmes. Based on South Africa’s ethnically diverse society, cultural differences pose various challenges for international students. This results in intercultural communication apprehension and therefore, a negative experience for international students. The aim of this research is to examine the cultural challenges faced by international exchange students studying at a university in South Africa. A quantitative descriptive methodology was employed for this study. Themes emanating from the literature review were used to develop a research questionnaire that consisted mostly of closed-ended questions followed by a few open-ended questions. The questionnaire was administered to ninety nine international students. The findings of the investigation indicate that the majority of international students experience culture as a challenge, which impacted on their ability to communicate and to be understood. To add credence to the international students’ experiences and the exchange programme, this paper therefore, suggests that issues around culture and intercultural communication is introduced as a core study module for all first-time international students before they arrive in South Africa.